Growth and Metabolite Enhancement of Acidophile Euglena sp. Isolated from Indonesia under Different Photoperiod Cycles - Erfianti, Tia; Daryono, Budi Setiadi; Budiman, Arief; Suyono, Eko Agus (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract Euglena sp. is a unicellular, flagellated microalga considered one of the most promising microalgal feedstock species for biofuels. Reducing the level of liquid waste pollutants can be done biologically by using microalgal organisms. Its metabolites, including lipids, proteins, carbohydrates, and pigments, are appropriate for producing biorefinery products such as biodiesel and jet fuels. They can be isolated from extreme environments, such as highly acidic and ammonia-rich environments, that are not conducive to their proliferation. This study sought to determine the effect of the photoperiod or (light: dark) cycle (24 L:0 D, 12 L:12 D, 14 L:10 D, and 16 L:8 D) on the growth, biomass, metabolite content consisting of lipids, carbohydrates, and proteins, and the rate of CO2 uptake by Euglena sp. As stated previously, the study was conducted by cultivating Euglena sp. on a laboratory scale with four photoperiod regimens. The results indicated that optimal growth, biomass content, and metabolite content were obtained with a 24 D:0 L lighting cycle. The control treatment (24 L: 0 D) had the highest biomass productivity (0.032 g.L-1.day-1 ± 0.004), lipid content (0.387 g.L-1 ± 0.031), protein content (0.542 mg.Ml-1 ± 0.007), carbohydrate content (0.409 x104 g.L-1), chlorophyll a (6.237 g.L-1 ± 0.184), chlorophyll b (2.838 g.L-1 ± 0.253), and total carotenoid (1.566 g.L-1 ± 0.105). Full light illumination (24 L:0 D) was significantly producing carotenoid content, including phaeophytin a, phaeophytin b, violaxanthin, 9'-cis-neoxanthin, dino xanthin, and fucoxanthin. Highlight Research The growth rate was higher when Euglena was cultivated under continuous illumination. The biomass productivity of Euglena increased significantly under continuous illumination. The metabolite content of Euglena (lipids, proteins, and pigments) was higher in continuous illumination.